Illicit Trade in Counterfeit Medicines: Challenges, Solutions, and a Case Study of Indonesia - Khwaileh, Khaled; Kazić-Çakar, Ena (Journal of Indonesian Legal Studies, 2025)
This paper examines the challenges posed by the trafficking of counterfeit medicines, particularly in developing countries affected by conflicts and challenging regimes. Counterfeit medicines imitate legitimate products, posing severe health risks to unsuspecting consumers. Criminal networks thrive in areas with weak regulations, governance, and enforcement capacity, taking advantage of chaos and limited oversight. Factors like corruption, porous borders, and high medicine costs further contribute to the spread of this illegal trade. The role of international organizations, such as the World Trade Organization (WTO), World Health Organization (WHO) and INTERPOL, in combating this crime is highlighted, emphasizing the need to strengthen enforcement efforts and enhance global cooperation. To address this significant global health threat, strict penalties, international collaboration, and prioritizing public health are crucial components of an effective approach. One avenue of change is that the developing countries be allowed to manufacture generic drugs but the World Trade Organization's Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and patent protections limits access to affordable medicines, hindering the production of generic drugs in poor countries. By ensuring access to affordable medicines, the international community can protect vulnerable populations and combat the trafficking of counterfeit medicines.